Corporate communication - Argenti, Paul A. (McGraw-Hill, 2016)
A comprehensive account of corporate communications, including both text and cases. Information new to this edition covers corporate philanthropy, government affairs and community relations. There is increased emphasis on communication strategy and four new business cases are included.